Anti-cancer and anti-angiogenesis effect of the leaf extract of Sargassum wightii against osteosarcoma cancer cells - Yu, Qi-Long; Tang, Zhao-Chun; Li, Jin-Ge; Wang, Guo-Liang; Wang, Pei-Jun; Pan, Zhao-Bao (Bangladesh Journal of Pharmacology, 2015)
This study was aimed to evaluate the chemical composition of ethanolic leaf extract of a marine macro-alga Sargassum wightii (ELESW) followed by its vascular endothelial growth factor (VEGF) induced anti-angiogenic effect against human umbilical vein endothelial cells (HUVECs). The effect of ELESW on cell viability and its potential against in vivo angiogenesis was assessed by using the MTT and CAM assay respectively. The phenolic, flavonoid, polysaccharides, and protein content of ELESW were found to be 56.0 ± 4.1 mg GAE/g, 26.3 ± 3.6 mg QE/g, 284.2 ± 6.2, 100.9 ± 8.9 ?g/mL, respectively. In angiogenesis, ELESW (100, 500 and 1,000 ?g/mL) significantly inhibited VEGF induced angiogenesis as well as VEGF-induced proliferation and tube formation of HUVECs in a dose-dependent manner. Upon stimulition by VEGF, HUVECs rapidly increased reactive oxygen species production, which was significantly blocked by treatment with ELESW. These findings suggesting that S. wightii could be a valuable candidate of therapeutic efficacy.